ショウワ キチ ニオケル VLF エミッション カンソク 1970 1971 1 オーロラヒス ト オーロラ ニホン ニホン ナンキョク チイキ カンソクタイ ノ ホウコク - 巻田, 和男; マキタ, カズオ; 福西, 浩; フクニシ, ヒロシ; MAKITA, Kazuo; FUKUNISHI, Hiroshi (国立極地研究所, 1973)
P(論文) VLF emissions were observed at Syowa Station by the 11th wintering party of the Japanese Antarctic Research Expedition in 1970-1971. The present paper deals particularly with the records of auroral hiss emissions, which are believed to be emitted by precipitating electrons in the aurora. It is shown that the power spectrum of the hiss emissions is confined in the low-frequency range between 4-32kHz if the auroral arcs lie near the poleward horizon of Syowa Station, while it is extended to frequencies as high as 128kHz if the active auroral arcs appear near the zenith. This can be explained by differences in the height of the emission region and in the propagation path of the hiss in the ionosphere : the high-frequency (～64kHz) hiss is emitted at low altitudes of 1000-1500km, its propagation path being limited to a narrow region near the location of the auroral arcs, while the low-frequency (～8kHz) hiss is emitted at higher altitudes of 3000-3500km, its propagation path spreading widely due to the refraction effect in the ionosphere. departmental bulletin paper